2004
DOI: 10.1080/0034340042000292656
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Competitive Strategy in Europe's Vulnerable Regions: Firm, Industry and Country Effects in Labour-intensive Industries

Abstract: Clark G. L., Palaskas T., Tracey P. and Tsampra M. (2004) Globalization and competitive strategy in Europe's vulnerable regions: firm, industry and country effects in labour-intensive industries, Regional Studies38, 1077-1092. European integration has prompted great interest in the adjustment capacities of small and medium enterprises in regions characterized by high levels of unemployment and lower-than-average incomes. At issue, in these circumstances, is the extent to which economic competitiveness can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
1
25
1
Order By: Relevance
“…National labour markets seem to be integrated; individuals care more about their relative skill compared to the country rather than to the region in which they live. This result is in line with Clark et al (2004) who found that there are significant country effects affecting European small and medium enterprises' competitive strategy in a global economy, including their demand for skilledlabour. Regarding the control variables, we find that age reduces the likelihood of supporting globalization until age 48, when age starts to increase the probability of favouring globalization.…”
Section: Skill and Support For Globalization In The Eusupporting
confidence: 93%
“…National labour markets seem to be integrated; individuals care more about their relative skill compared to the country rather than to the region in which they live. This result is in line with Clark et al (2004) who found that there are significant country effects affecting European small and medium enterprises' competitive strategy in a global economy, including their demand for skilledlabour. Regarding the control variables, we find that age reduces the likelihood of supporting globalization until age 48, when age starts to increase the probability of favouring globalization.…”
Section: Skill and Support For Globalization In The Eusupporting
confidence: 93%
“…Fitjar and Rodriguez-Pose (2011a;2011b) show how Norwegian firms develop strategies which overcome remoteness and facilitate innovation. Such studies support the idea that firms which neither sort into areas with characteristics they value, nor adopt strategies to compensate for particular locations, are less likely to survive (Clark et al, 2004).…”
Section: Firm Effects Sorting Adaptation and Survivalmentioning
confidence: 66%
“…In terms of local economic development, 'low-road' policy implies a narrow set of homogenized policy initiatives (Gordon, 1996;Helper, 2009), characterized by low-end prescriptive activities that propagate and are mimicked among many places (Malecki, 2004;Ornston, 2014). Alternatively, 'high-road' policies focus on comprehensive placed-based strategies to attract and retain mobile resources through enhancements and improvements to local conditions and attributes (Clark, Palaskas, & Tsampra, 2004;Helper, 2009;Malecki, 2004;Markusen, 1996;Turok, 2004). 'High-road' policies are more likely to be effective and provide the strongest opportunity for a place to be competitive (Clark et al, 2004;Malecki, 2004;Turok, 2004).…”
Section: Introductionmentioning
confidence: 99%